Justicia social en Iberoamérica: pobreza, desprecio y corrupción - Guadarrama González, Pablo; Mejía Quintana, Óscar; Rodríguez, Adriana Claudia; de la Fuente, José Alberto; Campos Rodrigo, Aníbal; Torres Galarza, Ramón; Obando Cabezas, Arístides; Álzate Castrillón, María Camila; Cruz Claros, Angie Vanessa; Hincapié Cetina, Diana; Fariñas Dulce, María José; Ferlin D’Ambroso, Marcelo José; et al. (Universidad Santiago de Cali, 2025)
Philosophers live in concrete worlds surrounded by their own and others' contingencies, which constitute the primary input for their critical observations, analyses, and reflections. For its part, a practical philosophy calls us to understand the contingencies that determine the possibilities of being and acting as individuals situated in time and space, in order to transform a sometimes pressing reality.